How is gastroesophageal reflux disease classified? - Akyüz, Filiz; Mutluay Soyer, Özlem (Turkish Journal of Gastroenterology, 2017)
Abstract Gastroesophageal reflux disease (GERD) is one of the most commonly diagnosed conditions in the daily practice of gastroenterologists. Due to variations in symptoms and clinical findings, differences in the severity of the disease in each patient and the fact that diverse methods are used for making a diagnosis makes a single and standard classification of this disease impossible. Here a step-approach suitable for GERD classification is summarized. Full Text Turkish